PTH-026 Water infusion enteroscopy – description of a new technique with first clinical results. (22nd June 2015) - Ishaq, S; Antonello, A; Grauer, M; Tontini, GE; Neumann, H
Abstract : Introduction: Device assisted enteroscopy is the standard technique to explore the deep small bowel. However, continuous insufflation of air often significantly distends the small intestine and hampers subsequent advancement of the enteroscope, resulting in distension related abdominal discomfort that can compromise the completion of the procedure and its diagnostic and therapeutic yield. We aimed at developing a novel water infusion technique to reduce small bowel distension and to facilitate enteroscopic procedures. Method: We have performed enteroscopies with water infusion in patients who underwent prior wireless capsule enteroscopy that yielded pathologic findings which required further evaluation and/or treatment. Once the enteroscope was passed through the pylorus CO2 insufflation was switched off. Subsequent advancement of the scope was performed with water infusion whenever necessary to visualise the intestinal lumen. Push-and-pull enteroscopy was performed as per the standard technique. The primary study end points were: system preparation time, rates of successful deep small bowel enteroscopy, procedure duration, diagnostic and therapeutic yield, rate of adverse events. The secondary endpoints included subjective evaluations by the patients concerning the discomfort associated with the procedure and by the endoscopist concerning the ease of performing the procedure. Results: Water infusion enteroscopies were performed in 4 patients. The median age of the patients included in the study was 62 (range 36–72). Median time to prepare the system was 2 min (Range 2–3). Enteroscopy was performed successfully in all cases. The estimated median small bowel intubation depth – past the ligament of Treitz- was 160 cm (Range 145–220 cm). Median time of the procedure was 14 min (Range 14–16). All the procedures provided diagnostic elements or enabled treatment. No complications occurred during or after the procedure. Endoscopic findings and treatments are described in the table. Patients reported no significant discomfort during and after the procedure, and endoscopists were able to complete the procedure with ease in all patients. Endoscopic findings and treatments Conclusion: The newly introduced water infusion technique allows for deep small bowel enteroscopy within a relatively short period of time. This procedure is relatively safe and well tolerated. Further studies are needed to assess the efficacy and safety of Disclosure of interest: None Declared.